Anti-depressant-like effects of rannasangpei and its active ingredient crocin-1 on chronic unpredictable mild stress mice - Du, Yang; Wang, Yan-Li; Chen, Lei; Li, Qi-En; Cheng, Yong (Frontiers in Pharmacology, 2023)
Major depressive disorder is one of the most common neuropsychiatric diseases and it is a global public health problem that leads to disabilities. Currently, there is a growing need to explore novel strategy to cure major depressive disorder due to the limitation of available treatments. Rannasangpei (RSNP) is a traditional Tibetan medicine which acts as a therapeutic agent in various acute or chronic diseases, including cardiovascular diseases and neurodegenerative diseases. Crocin-1 a coloring ingredient of saffron which exhibited anti-oxidative and anti-inflammatory properties. Here, we aimed to illustrate whether RSNP and its active ingredient crocin-1 rescue depressive-like phenotypes in chronic unpredictable mild stressed (CUMS) induced mouse model of depression. Our results showed that peripheral administration of RSNP or crocin-1 ameliorated the depressive-like behaviors in CUMS-treated mice, as demonstrated by the forced swimming test and tail suspension test. Furthermore, RSNP or crocin-1 treatment reduced oxidative stress in the peripheral blood and hippocampus of the CUMS-treated mice. Additionally, the dysregulated immune system response, as demonstrated by the increased expression of the pro-inflammatory factors (tumor necrosis factor-α and interleukin-6) and the decreased expression of the anti-inflammatory factor-interleukin-10 in the prefrontal cortex and/or hippocampus of CUMS-treated mice, were at least partially restored by RSNP or crocin-1 treatment. RSNP or crocin-1 also restored apoptotic protein marker (Bcl-2 and Bax) levels in the prefrontal cortex and hippocampus of the CUMS-treated mice. Moreover, our data indicated that RSNP or crocin-1 increased astrocyte proliferation and brain-derived neurotrophic factor levels in the hippocampus of CUMS-treated mice after RSNP or crocin-1 administration. Taken together, our study for the first time revealed an anti-depressant effect of RSNP and its active ingredient crocin-1 in a mouse model of depression, with involvement of oxidative stress, inflammatory response and apoptotic pathway.